Influence of capping on the atomistic arrangement in palladium nanoparticles at room temperature - Corthey, Gastón; Olmos Asar, Jimena A.; Casillas, Gilberto; Mariscal, Marcelo M.; Mejía Rosales, Sergio; Azcárate, Julio César; Larios, Eduardo; Yacamán, Miguel José; Salvarezza, Roberto; Fonticelli, Mariano H. (American Chemical Society, 2014)
The role that protecting molecules have on the way that palladium atoms arrange themselves in nanoparticles prepared at room temperature was studied by the analysis of aberration-corrected scanning transmission electron microscopy images and atomistic Langevin dynamics simulations. It was found that the arrangement of Pd atoms is less ordered in thiolate-protected nanoparticles than in amine-protected ones. The experimental and theoretical data showed that the disorder in ∼3 nm thiolate-protected particles is promoted by the strong S−Pd bond in the sulfide layer that surrounds the nanoparticles.